The Treatment of Refractory Pituitary Adenomas - Dai, Congxin; Liu, Xiaohai; Ma, Wenbin; Wang, Renzhi (Frontiers in Endocrinology, 2019)
Refractory pituitary adenomas (PAs) are defined as aggressive PAs characterized by a high Ki-67 index, rapid growth, frequent recurrence, and resistance to conventional treatments. It is notoriously difficult to manage refractory PAs because the efficacy of current therapeutic options is limited. The purpose of this review is to address currently employed and promising therapeutic strategies for the treatment of refractory PAs. Except for prolactinomas, neurosurgery is the first-line option, but most refractory PAs often recur or regrow after initial surgery and require repeated surgery. Medical therapy and radiotherapy are explored when surgery has failed to completely resect tumors; however, refractory PAs are usually resistant to medications and radiotherapy. As a salvage treatment, temozolomide (TMZ) has shown promising results and is currently used for all types of refractory PAs. However, not all refractory PAs are responsive to TMZ treatment, and some of these PAs are resistant to TMZ. Although targeted therapies such as vascular endothelial growth factor, epidermal growth factor and mTOR inhibitors have also been used to treat refractory PAs, the effectiveness of these targeted therapies is still not known due to a lack of data from randomized prospective trials. As a novel therapeutic method, cancer immunotherapy is a promising strategy for the treatment of refractory PAs, but further preclinical research and clinical trials are needed to assess the efficacy of this new approach. In summary, early identification and a multidisciplinary approach are required to treat refractory PAs.